2020
DOI: 10.12944/carj.8.2.08
|View full text |Cite
|
Sign up to set email alerts
|

Variation Among Poplar (Populus Deltoides Bartr.) Clones for Growth, Wood Traits and Tolerance to Leaf Spot Diseases

Abstract: Poplar is economically important and fast growing tree species which is widely adopted by farmers of northwest India. The nursery study was conducted for two years to find out clonal variation for plant height, collar diameter, biomass, wood traits and incidence of leaf spot disease. Results found significant differences among the clones for all growth traits, specific gravity and fiber length. Clones L-290/84, 22-N and L-50/88 were promising for tree height and collar diameter during 1st year study. In 2nd ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
2
4
0
Order By: Relevance
“…A list of different Clones of poplar (Populus deltoides) The present study showed that ample variation exists among the clones for height and diameter. The reported variations among poplar clones under study are in line with the findings ofPuri et al (2002),Ozel et al (2010) andDhillon et al (2020) in poplar.…”
supporting
confidence: 89%
“…A list of different Clones of poplar (Populus deltoides) The present study showed that ample variation exists among the clones for height and diameter. The reported variations among poplar clones under study are in line with the findings ofPuri et al (2002),Ozel et al (2010) andDhillon et al (2020) in poplar.…”
supporting
confidence: 89%
“…The main genera are known to cause moderate, non-fatal damage: Alternaria generally causes crown diseases of aspen infecting leaves and branches, and Fusarium spp. infection symptoms include the yellowing and wilting of leaves, cankers, and necrosis [54][55][56][57][58]. Accordingly, most represented genera belonged to weak pathogen groups that consequently have a low direct impact on timber quality.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted by Nicodemus et al (2014) [26] showed dbh growth of only 6.5cm in a four-years old plantation for clones of Casuarina junghuhniana. [6] and Tomar et al (2020) [34] for growth performance of Populus clones. The number of trees per area (stand density or spacing) has a significant impact on the yield of tree plantations (Evans, 2009) [8] .…”
Section: Discussionmentioning
confidence: 99%